Biogeographic comparisons of herbivore attack, growth and impact of Japanese knotweed between Japan and France. (21st December 2012) - Maurel, Noëlie; Fujiyoshi, Masaaki; Muratet, Audrey; Porcher, Emmanuelle; Motard, Eric; Gargominy, Olivier; Machon, Nathalie; Callaway, Ray
Summary To shed light on the process of how exotic species become invasive, it is necessary to study them both in their native and non‐native ranges. Our intent was to measure differences in herbivory, plant growth and the impact on other species in Fallopia japonica in its native and non‐native ranges. We performed a cross‐range full descriptive, field study in Japan (native range) and France (non‐native range). We assessed DNA ploidy levels, the presence of phytophagous enemies, the amount of leaf damage, several growth parameters and the co‐occurrence of Fallopia japonica with other plant species of herbaceous communities. Invasive Fallopia japonica plants were all octoploid, a ploidy level we did not encounter in the native range, where plants were all tetraploid. Octoploids in France harboured far less phytophagous enemies, suffered much lower levels of herbivory, grew larger and had a much stronger impact on plant communities than tetraploid conspecifics in the native range in Japan. Our data confirm that Fallopia japonica performs better – plant vigour and dominance in the herbaceous community – in its non‐native than its native range. Because we could not find octoploids in the native range, we cannot separate the effects of differences in ploidy from other biogeographic factors. To go further, common garden experiments would now be needed to disentangle the proper role of each factor, taking into account the ploidy levels of plants in their native and non‐native ranges. Synthesis. As the process by which invasive plants successfully invade ecosystems in their non‐native range is probably multifactorial in most cases, examining several components – plant growth, herbivory load, impact on recipient systems – of plant invasions through biogeographic comparisons is important. Our study contributes towards filling this gap in the research, and it is hoped that this method will spread in invasion ecology, making such an approach more common.